2013
DOI: 10.1016/j.crvi.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Profil parasitologique de deux formes de schistosomiase (formes urinaire et intestinale) dans dix sites du Burkina Faso (pays d’Afrique sub-saharienne)

Abstract: Profil parasitologique de deux formes de schistosomiase (formes urinaire et intestinale) dans dix sites du Burkina Faso (pays d'Afrique subsaharienne)Parasitological profile of two forms of schistosomiasis (urinary and intestinal forms) at ten sites in Burkina Faso (Sub-Saharan Africa country

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…7b). Similar results were found by Takougang et al (1993) in the extreme North of Cameroon and by Zongo et al (2012) over 10 sites in Burkina Faso.…”
Section: Influence Of Air Temperature On Children Behavioursupporting
confidence: 80%
See 3 more Smart Citations
“…7b). Similar results were found by Takougang et al (1993) in the extreme North of Cameroon and by Zongo et al (2012) over 10 sites in Burkina Faso.…”
Section: Influence Of Air Temperature On Children Behavioursupporting
confidence: 80%
“…Two years after in 2002 prevalence were 43.4 and 90.8 %, respectively (Poda et al 2004). Zongo et al (2012) indicated a global prevalence of 3 % for S. haematobium among school aged children in the Sourou Valley and within a particular context of mass drug administration with praziquantel. These authors have also observed that in general in Burkina Faso, prevalence of S. haematobium is decreasing while that for S. mansoni is increasing.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The ovular transmission is higher among girls than boys in both agro-ecosystems. Zongo et al (2012), Yapi et al (2014) reported a difference in prevalence by gender in Sahel with a higher infection in men than women. Socioanthropological surveys would provide clarification on the behavior of both sexes in contamination sources.…”
Section: S Heamatobium Eggs Load S Mansoni Eggs Loadmentioning
confidence: 99%